ANALYSIS OF SENSATIONS AROUND THE TRINITY DOCTRINE IN INDONESIA - Georges Nicolas Djone; Leyna Christin Nainggolan; Wahyu Juli Suryaningsih; Weni Lolinga; Tirza Manaroinsong (CV. Ulil Albab Corp, 2022)
The purpose of writing this article is to examine the controversy over the doctrine of the Trinity Doctrine today, as well as to analyze the relevance of the urgency of liberation theology to this teaching today, using a descriptive qualitative method approach through literature analysis and data collection techniques through Bible sources, various books, and journals, as well as various documents related to the object of research. As a result, there is a massive effort to evoke Sabellianism in terms known as